PELAKSANAAN REDISTRIBUSI TANAH DALAM RANGKA REFORMA AGRARIA DI KABUPATEN KUBU RAYA : Implementation of Land Redistribution in The Framework of Agrarian Reform in Kubu Raya District - Deviana Putri; Endang Pandamdari (Universitas Trisakti, 2024)
The agrarian reform program launched by the government basically aims to improve the welfare of the people, especially landless farmers. Through Presidential Regulation Number 86 of 2018 concerning Agrarian Reform, the government is trying to redistribute land for farmers, including those carried out in Kubu Raya Regency. However, in practice the land redistribution program carried out by the government isn’t in accordance with the procedures stipulated in Presidential Regulation Number 86 of 2018. Of the 10 access arrangement activities as stated in Presidential Regulation Number 86 of 2018, only 2 activities were carried out by Kubu Raya District Land Office. Before carrying out the implementation of land redistribution, the Land Office must first make a plan which is preceded by the preparation of operational instructions. Counseling on land redistribution activities should be carried out at the planning stage. In practice, the Kubu Raya Land Office doesn’t go through established mechanisms or procedures and directly conducts counseling at the implementation stage of activities that should have been carried out at the planning stage. In addition, the Land Office doesn’t control land whose area exceeds the maximum land ownership limit, which the government wants to control through the agrarian reform program.